Aggressive behavior of macaques, Macaca fascicularis (Raffles, 1821) on tourists at Kaliurang nature recreation forest, Yogyakarta - DJUWANTOKO DJUWANTOKO; RETNO NUR UTAMI; WIYONO WIYONO (Society for Indonesian Biodiversity, 2008)
Research was conducted in Kaliurang nature recreation forest area, in Gunung Merapi National Park, Yogyakarta. The research aim to investigate the proportion of aggressive behavior of monkeys [Macaca fascicularis (Raffles, 1821)] to tourists. Direct observation method was used to observe the monkeys behavior in the interaction to the tourists. And questioners were distributed to the tourists to know expectation of the tourists which related to the existence of the monkeys in that conservation area. Analyses of the interactions suggest thatmonkeys respond differentially to tourists according to the age/sex classes involved. Additionally, adult and subadult male monkeys participated in more aggressive behaviors than expected, while adult female monkeys and immature participated in such behaviors less than expected. These variations in interaction patterns between monkeys and tourists may have substantial implications for management issues and that the potential for gaining or reducing the tourists to visit in that forest recreation.Key words: monkey, Macaca fascicularis (Raffles, 1821), tourists, aggression; tourists-monkeys interactions.